Family structure of the Malaysian Indian youth involved in gangsterism - Suppiah, Veera Sundari; Muthusamy, Paramasivam; Ismail, Ismi Arif Bin (Human Resource Management Academic Research Society, 2021)
Gang culture and gangsterism among Indian youth has become very popular in the country over the past few years. This study attempts to describe the effect of family structure on the Indian youths who are involved in gangsterism. The study employs an inductive approach based on a combination of subjectivism and interpretivist philosophies in a qualitative research (semi structured, face to face individual interview guide). The findings showed that the family has direct and incredible influences to initiate them into crime. Their childhood and family background, their current family relationships, and associations between background or family characteristics are being the main factor. The failure to provide proper communication and a concrete family structure tremendously increases the ratio of youngsters engaging in gangsterism. The data for this study were collected from the Indian youths’ those are already members of gangs and practice gangsterism.